Issue Information TOC. Issue 1 (3rd September 2019) - Unknown
Abstract : Cover : In Soh and Wallace (https://doi.org/10.1002/cpcy.63 ), Quality assessment of bone marrow samples based on the recovery of mast cells, hematogones, and erythroid precursors. All plots shown are gated on R1 & R2 & R3 and NOT R4 & R5 & R6. (A ) Mast cells (defined as CD27–, CD117br) are identified by drawing an elliptical region (R8) on a bivariate plot of CD27 BV510 versus CD117 APC. (B ) An elliptical region (R9) is placed on a bivariate plot of SSC‐A versus CD45 PCPCy5.5 to identify erythroid precursors (defined as CD45–, SSClo). (C and D ) B cells (defined as CD56–, CD19+) are identified by placing a rectangular region (R10) on a bivariate plot of CD56 PE versus CD19 PECy7. B cells are then delineated using a bivariate plot of CD45 PCPCy5.5 versus CD81 APCH7. A region (R11) is then drawn to identify hematogones (defined as CD45dim, CD81br). See e63.